The Effect of Passive Design Strategies on Thermal Performance of Female Secondary School Buildings during Warm Season in a Hot and Dry Climate - Zahiri, Sahar; Altan, Hasim (Frontiers in Built Environment, 2016)
This paper describes a series of field studies and simulation analysis to improve the thermal performance of school buildings in the city of Tehran in Iran during warm season. The field studies used on-site measurement and questionnaire-based survey in the warm spring season in a typical female secondary school building. The on-site monitoring assessed the indoor air temperature and humidity levels of six classrooms while the occupants completed questionnaires covering their thermal sensations and thermal preferences. Moreover, thermal simulation analysis was also carried out to evaluate and improve the thermal performance of the classrooms based on the students’ thermal requirements and passive design strategies. In this study, the environmental design guidelines for female secondary school buildings were introduced for the hot and dry climate of Tehran, using passive design strategies. The study shows that the application of passive design strategies including south and south-east orientation, 10cm thermal insulation in wall and 5cm in the roof, and the combination of 30cm side fins and overhangs as a solar shading devices, as well as all-day ventilation strategy and the use of thermal mass materials with 25cm-30cm thickness, has considerable impact on indoor air temperatures in warm season in Tehran and keeps the indoor environment in an acceptable thermal condition. The results of the field studies also indicated that most of the occupants found their thermal environment not to be comfortable and the simulation results showed that passive design techniques had a significant influence on the indoor air temperature and can keep it in an acceptable range based on the female students’ thermal requirement. Therefore, in order to enhance the indoor environment and to increase the learning performance of the students, it is necessary to use the appropriate passive design strategies, which also reduce the need for mechanical systems and therefore reduce the energy loads of the building.